THE ROLE OF VIDEO ANALYSIS ON THE ACCURACY OF THE PASS OF THE ATHLETES WHO PRACTICE THE VOLLEYBALL GAME - Onesim Florin (Editura Univeristatii "Stefan cel Mare" din Suceava, 2020)
In this paper we tried to highlight the fact that the means obtained through video analysis can be defining in the qualitative increase of two-handed passes in the game of volleyball. The results obtained after the pedagogical approach confirmed the fact that the hypothesis from which it was started is valid and that the experiment was a success. The value of t control is better than t table.